Active faults studies in Delhi and national capital region (NCR): Inferences from satellite data and field investigations - Dhali, Mitthu; Gadhavi, Mahendrasinh S.; Mohan, Kapil; Narayana, Pitta Poorvi; Malik, Javed N. (Frontiers in Earth Science, 2023)
In recent years, the National Capital Region (NCR) of Delhi has experienced several earthquakes ranging in magnitude from 1.0 to 6.7. According to the last 50 years of earthquake data, the majority of earthquakes in the NCR have occurred near the Mahendragarh Dehradun Fault (MDF) and the Sohna Fault (SF). The region is bounded by a number of subsurface Ridges, Faults, and Lineaments, which are also influenced by the active plate boundary of the Indian and Eurasian plates. Active fault mapping is critical for the precise identification and marking of active fault traces in the NCR area for a precise seismic hazard assessment. We used high resolution Cartosat-1 stereopair data obtained from NRSC, Hyderabad, and Anaglyph (A 3D representation of the surface) and DEM prepared with ENVI software to map the active faults. We identified 12 sites in the NCR region based on satellite data interpretation, primarily along the MDF and Sohna Fault and their extensions. The presence of tectono-geomorphic markers along the MDF and Sohna Fault, such as warped surfaces indicative of fault scarps, stream offsets, gully erosion, and sag ponds, suggests active tectonic movement along these faults, most likely in the recent geological past. We believe the MDF is a right-lateral strike-slip fault with a compressional component on the western side and an extensional component on the eastern side. It acts as a segment boundary between compressional and extensional boundaries. We also identified the right lateral Nuh-Jhirka fault (NJF), which can be the Sohna Fault's southern extension from Nuh to Jhirka. The western limb of the Delhi Mega fold has also seen a few right-lateral strike-slip movements that have extended up to the eastern bank of the Yamuna River, where the river reflects the base-level change and tight meandering on its upward side and a straight pattern on its downward side. This fault is known as the Delhi Fault (DF). The findings are preliminary, and further research would be required to create a detailed active fault map of the Delhi-NCR region to conduct a precise Seismic Hazard Assessment (SHA) of the region.